Technische Bildung im Sachunterricht der Grundschule Elementar bildungsbedeutsam und dennoch vernachlässigt? - Landwehr, Brunhild; Mammes, Ingelore; Murmann, Lydia (Forschungen zur Didaktik des Sachunterrichts, 2021)
Technical education in primary school is a relevant topic for the Gesellschaft für Didaktik des Sachunterrichts (Society for the Didactics of Science Education in Primary Schools) - this is already shown by the designation of a separate perspective in the Perspektiverahmen Sachunterricht. However, research results in the field of technical learning can currently only be found sporadically. In research conferences on technical education that have been taking place since 2017, colleagues have presented research projects on children's learning preconditions and conditions, the impact of teaching settings, the importance of the interplay between thinking and acting, the importance of language in technical learning, children's abilities in the area of analytical thinking, etc. In addition, colleagues posed the question of how and whether schools have equipment available that would make technical education possible in the first place. These perspectives and (preliminary) research findings are summarised in this volume.